Seven-Year Follow-Up of a Patient With a Retained Needlefish Jaw Fragment Abutting Against His Left Internal Carotid Artery. Issue 2 (June 2021) - Daigle, Patrick; Mehta, Sonul; Bhayana, Rajesh; Das, Sunit; Bharatha, Aditya; Nijhawan, Navdeep
Abstract : Abstract: A 51-year-old man presented to the ophthalmology service with binocular diplopia and facial numbness. The patient was returning from a trip to Mexico. He reported having been hit in the left periocular region by a fish while swimming. Local doctors repaired a laceration in the left lateral canthus shortly after the incident. Orbital imaging revealed 2 needle-like foreign bodies corresponding to retained pieces of a needlefish jaw in the left orbit. Given the location of the foreign bodies, observation with repeat imaging was deemed more appropriate than surgical exploration. Subsequent imaging studies showed no migration of the foreign body, and the patient did not suffer from any related complications more than 7 years after the initial injury.